2022
DOI: 10.21037/apm-21-341
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis with systemic lupus erythematosus: case report and review of the literature

Abstract: Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are potentially fatal mucocutaneous diseases characterized by extensive necrosis and exfoliation of the epidermis. TEN and SJS are most often caused by various kinds of drugs. Other risk factors for SJS/TEN include pneumonia infection, HIV infection, genetic factors, underlying immune diseases, and tumors. SJS and TEN were first identified in 1922, but at present, a widely recognized view is that SJS and TEN represent phases in the continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The diagnosis of lupus-induced SJS/TEN and classical SJS/TEN is difficult. Lupus-induced SJS/TEN was a subacute presentation of weeks without systemic involvement and no history of drug ingestion [ 11 ]. Classical TEN was acute evolution within 3–4 days or sometimes hours, with a close drug-related causality and negative immunofluorescence [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of lupus-induced SJS/TEN and classical SJS/TEN is difficult. Lupus-induced SJS/TEN was a subacute presentation of weeks without systemic involvement and no history of drug ingestion [ 11 ]. Classical TEN was acute evolution within 3–4 days or sometimes hours, with a close drug-related causality and negative immunofluorescence [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found the culprit drugs that were at high risk for triggering SJS were phenytoin, lamotrigine, and allopurinol [21,22]. An increased risk for developing SJS is associated with factors such as age, autoimmune disease, previous drug allergies, epilepsy, or a history of cerebrovascular accident [23][24][25].…”
Section: Review Stevens-johnson Syndromementioning
confidence: 99%
“…El diagnóstico es clínico y a través de biopsia de la piel con tinción de hematoxilina-eosina. (Hasegawa et al., 2022; Wung et al, 2022)Se utiliza la escala de SCORTEN para determinar la probabilidad de muerte en NET (Fan et al, 2022;Cetin et al;2013)…”
unclassified